Pemenuhan Kebutuhan Dasar Manusia Pada Lansia Demensia Oleh Keluarga - Dwiyani Kartikasari; Fitria Handayani (Jurnal Keperawatan Diponegoro, 2012)
Basic human needs are the elements needed by man to maintain life and health. According to Abraham Maslow basic human needs consist of physiological needs, self security needs, love and belonging needs,self esteem, and self actualization. Dementia is a condition in which a person experiences gradual decline or cognitive impairment that will eventually decrease this ability. so as to interfere his or him the activity and cause a lack of fulfillment of basic needs of among elderly. The purpose of the study was to find a picture of the frequency of fulfillment of basic human needs of the elderly with dementia in the Posyandu elderly Tembalang Village. The design used in the research is descriptive and mean while the method used is cross sectional approach. Sampling technique uses total sampling, with 32 people. In analyze the data the researcher uses descriptive analysis. These results of the research shows that, 59,4% the physiological needs was fulfilled, 56,2% the self security needs was not fulfilled, 56,2% the love and belonging needs was fulfilled,  59,4% the self esteem needs was fulfilled, and 46,9% the self actualization needs was not fulfilled. The role of family as a support system in the fulfillment basic human needs of the elderly with dementia that registered in Posyandu elderly Tembalang village.